Virtual Store Experience: Will it increase the intention to visit the physical store or make a purchase? - Florensi, Felicia (AIBPM Publisher, 2022)
Covid-19 affected consumer behavior, especially in the first year. Expectations and consumer habits in grocery shopping are switched over. Government regulations limit our outside activities caused consumer demand for omnichannel shopping experience or online and offline shopping availability at once (Economist, 2021).A physical store is still an option for a multichannel company and will give a unique value to the brand (Bella, 2019). The consumer will be more pleased to evaluate online stores after having experience from a physical store (Baek, 2020). Physical stores and online stores are complementary (Fornari, 2016).To persuade the consumer to come to a physical store, many retail players have tried to implement a virtual tour experience since it enables the consumer to experience a certain store or place without having to visit it physically. The virtual tour uses a computer to present a virtual environment with 360degree media, online media, and virtual reality tech without the need to attend physically. As part of the brand experience, virtual tours influence brand equity and increase visit intention (Baek, 2020). Positive experience with store brands also influences purchase intention (Diallo, 2017). The higher the brand equity, the higher motivation, preference, and desire to purchase (Pappu, 2005).